Effects of 1,1,1-Trichloroethane and Triclocarban on Reductive Dechlorination of Trichloroethene in a TCE-Reducing Culture - Wen, Li-Lian; Chen, Jia-Xian; Fang, Jia-Yi; Li, Ang; Zhao, He-Ping (Frontiers in Microbiology, 2017)
Chlorinated compounds were generally present in the environment due to widespread use in the industry. A short-term study was performed to evaluate the effects of 1,1,1- trichloroethane (TCA) and triclocarban (TCC) on trichloroethene (TCE) removal in a reactor fed with lactate as the sole electron donor. Both TCA and TCC inhibited TCE reduction, but the TCC had a more pronounced effect compared to TCA. The TCE-reducing culture, which had never been exposed to TCA before, reductively dechlorinated TCA to 1,1-dichloroethane (DCA). Below 15 µM, TCA had little effect on the transformation of TCE to cis-dichloroethene (DCE); however, the reduction of cis-DCE and vinyl chloride (VC) were more sensitive to TCA, and ethene production was completely inhibited when the concentration of TCA was above 15 M. In cultures amended with TCC, the reduction of TCE was severely affected, even at concentrations as low as 0.3 µM; all the cultures stalled at VC, and no ethene was detected. The cultures that fully transformed TCE to ethene contained 5.2 - 8.1% Dehalococcoides. Geobacter and Desulfovibrio, the bacteria capable of partially reducing TCE to DCE, were detected in all cultures, but both represented a larger proportion of the community in TCC-amended cultures. All cultures were dominated by Clostridium_sensu_stricto_7, a genus that belongs to Firmicutes with proportions ranging from 40.9% (in a high TCC (15 M) culture) to 88.2%. Methanobacteria was detected at levels of 1.1% to 12.7%, except in cultures added with 15 and 30 M TCA, in which they only accounted for 0.4%. This study implies further environmental factors needed to be considered in the successful bioremediation of TCE in contaminated sites.